PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA SISWA KELAS V SDN 13 TRANS RANGKANG - Yulianti Yulianti; Kusnanto (STKIP Subang, 2026)
This classroom action research aimed to improve fifth-grade students’ learning outcomes in Pancasila Education through the Jigsaw cooperative learning model. The study was conducted at SDN 13 Trans Rangkang involving 27 students. Data were collected through observation and learning achievement tests. The research was implemented in two cycles consisting of planning, action, observation, and reflection. Initial findings showed low learning outcomes with an average score of 61.63 and only 30% of students achieving mastery. The implementation of the Jigsaw model increased student participation, collaboration, and understanding of learning materials. The findings indicate that the Jigsaw cooperative learning model can improve students’ learning outcomes in Pancasila Education.